2020
DOI: 10.1002/eji.201948299
|View full text |Cite
|
Sign up to set email alerts
|

Bcl6 modulates innate immunity by controlling macrophage activity and plays critical role in experimental autoimmune encephalomyelitis

Abstract: The B‐cell CLL/lymphoma 6 (Bcl6) oncogenic repressor is a master regulator of humoral immunity and B‐cell lymphomagenesis. Although much research has focused on its regulation and function of GC B cells and T cells, the role of Bcl6 in regulating the functions of innate immunity is not well defined. Here, we demonstrated that EAE is exacerbated in LysM Cre+/− Bcl6fl/fl mice. Although other cells such as neutrophils might be involved in this conditional mutant mouse model, we found that the disease pathology is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…The action of anti-inflammatory Mφ is pivotal in the prevention and treatment of inflammatory-related diseases. [31][32][33] Our previous study had demonstrated that, similar to MSCs, adoptive transfer of MSCs-educated Mφ attenuated inflammation and kidney injuries in STZ-induced DN mice. 17 PGC-1α has been demonstrated to drive mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The action of anti-inflammatory Mφ is pivotal in the prevention and treatment of inflammatory-related diseases. [31][32][33] Our previous study had demonstrated that, similar to MSCs, adoptive transfer of MSCs-educated Mφ attenuated inflammation and kidney injuries in STZ-induced DN mice. 17 PGC-1α has been demonstrated to drive mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR5, BCL‐6) does not completely inhibit the function of germinal centres [ 98 ]. Beyond, there are substantial differences between in vivo and in vitro studies investigating T FH cells, and molecules regulating the development of T FH cells such as BCL‐6, ICOS, CXCL13, CXCR5, IL‐21/IL‐21R, PD‐1/PD‐L1 have opposite roles during EAE development [ 94 , 109 , 112 , 113 , 114 , 115 ], possibly reflecting the heterogeneity of T FH cells in different MS‐related animal models. Finally, these molecules are not specific to T FH cells and their inhibition can affect a variety of other cells and cellular interactions.…”
Section: Insights Into Elfs From Animal Studiesmentioning
confidence: 99%
“…B-cell lymphoma 6 (BCL6) is a sequence-specific transcriptional regulator that inhibits the transcription of target genes by binding to a specific DNA sequence in the promoter region ( 24 , 25 ). BCL6 serves an important role in the development of B cells, follicular Th cells and T regulatory cells, indicating its potential function in regulation of the immune response ( 26 28 ).…”
Section: Introductionmentioning
confidence: 99%